A Reconfigurable MIMO Antenna System for Wireless Communications - Evizal Abdul Kadir (IAES Indonesia Section, 2017)
A reconfigurable antenna system is proposed to improve data throughput limitations in multiple input multiple output wireless communication systems in this investigation. The4×4 MIMO antenna is designed to operate in the 2.4 and 2.6 GHz for Wireless Local Area Network (WLAN) and Long TermEvolution (LTE) applications. The system’s radiation pattern re-configurability is realized by using the microcontroller-drivenPIN diode switching concept. Simulations and measurements exhibited good agreements for the single, 2×2 MIMO and 4×4MIMO configurations. The antenna is operational between 2.387to 2.628 GHz, while the simulated and measured reflection coefficients are at least -24.3 dB. All configurations produced anarrow beam forward radiation, while the envelope correlation coefficient (ECC) and diversity gain for the two MIMO configurations are below 0.5 and at least 9 dBi, respectively.